Colonic stenting in acute malignant large bowel obstruction: audit of efficacy and safety in a Singapore tertiary referral centre - James Weiquan Li; James Chi-Yong Ngu; Kok Ren Lim; Shu Wen Tay; Bochao Jiang; Ramesh Wijaya; Sulaiman Yusof; Calvin Jianming Ong; Andrew Boon Eu Kwek; Tiing Leong Ang (Singapore Medical Journal)
Introduction: Acute malignant large bowel obstruction (MBO) occurs in 8%–15% of colorectal cancer patients. Self-expandable metal stents (SEMS) have progressed from a palliative modality to use as bridge to surgery (BTS). We aimed to assess the safety and efficacy of SEMS for MBO in our institution. Methods: The data of patients undergoing SEMS insertion for MBO were reviewed. Technical success was defined as successful SEMS deployment across tumour without complications. Clinical success was defined as colonic decompression without requiring further surgical intervention. Rates of complications, median time to surgery, types of surgery and rates of recurrence were studied. Results: Seventy-nine patients underwent emergent SEMS placement from September 2013 to February 2020. Their mean age was 68.8 ± 13.8 years and 43 (54%) patients were male. Mean tumour length was 4.2 cm ± 2.2 cm; 89.9% of malignant strictures were located distal to the splenic flexure. Technical and clinical success was 94.9% and 98.7%, respectively. Perforation occurred in 5.1% of patients, with none having stent migration or bleeding. Fifty (63.3%) patients underwent SEMS insertion as BTS. Median time to surgery was 20 (range 6–57) days. Most (82%) patients underwent minimally invasive surgery. Primary anastomosis rate was 98%. Thirty-nine patients had follow-up beyond 1-year posttreatment (median 34 months). Local recurrence and distant metastasis were observed in 4 (10.3%) and 5 (12.8%) patients, respectively. Conclusion: Insertion of SEMS for acute MBO has high success rates and a good safety profile. Most patients in this audit underwent minimally invasive surgery and primary anastomosis after successful BTS.